Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT. PLN (Persero) Area Lubuk Pakam - Catrin Novrista Harni; Fivi Rahmatus Sofiyah (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT   This research aims to determine and analyze how much influence the quality of service which covers tangible, reliability, responsiveness, assurance and emphaty to the level of satisfaction felt by customers who use services of PT. PLN (Persero) Area Lubuk Pakam. The observation is an assosiative one, that is an observation which looks for the relation between one variable with another variable. The population in this observation is the customers of PT. PLN (Persero) Area Lubuk Pakam. The collecting of primary data is done by using questionnaire which is measured by Likert scale. The observation uses descriptive analysis and doubled regressive linear analysis method. The result of this observation shows that the independent variable (quality of services) which covers tangible, reliability, responsiveness, assurance, and emphaty simultaneously give a positive and significant influence to the depent variable that is customers satisfaction. Through the testing of coefficient determination (R2), it is found that value of R = 0,761, which means that is a firm relation among quality of services to the customers satisfaction at PT. PLN (Persero) Area Lubuk Pakam, that is 76,1%. The result of data analysis with significant test partially show that tangible, reliability, and responsiveness is not positive and significant influence to the customers satisfaction. Assurance and emphaty there is a positive and significant influence to the customers satisfaction. Keywords: Customers Satisfaction, Quality of Services, Tangible, Reliability,  Responsiveness, Assurance, Emphaty.